Influence of macro- and microelements on the growth dynamics of potato crops on the 60th day after planting - А. V. КОVАL (Передгірне та гірське землеробство і тваринництво)
Studies of the influence of growth regulators and microfertilizers with L-a-amino acids on potato yield were conducted in the crop rotation of the sector of potato study of the Institute of Agriculture of the Carpathian region of NAAS in the Western Forest-Steppe zone on gray forestal soils.